2021
DOI: 10.3390/molecules26123610
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Drug Delivery System Based on Pluronics for Cancer Treatment

Abstract: Pluronic polymers (pluronics) are a unique class of synthetic triblock copolymers containing hydrophobic polypropylene oxide (PPO) and hydrophilic polyethylene oxide (PEO) arranged in the PEO-PPO-PEO manner. Due to their excellent biocompatibility and amphiphilic properties, pluronics are an ideal and promising biological material, which is widely used in drug delivery, disease diagnosis, and treatment, among other applications. Through self-assembly or in combination with other materials, pluronics can form n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…Different types of active principles can be solubilized within the PPO hydrophobic core [ 14 ] or can be conjugated to the PEO corona [ 15 ]. The loading of hydrophobic molecules in this type of PMs, with sizes usually smaller than 100 nm, can increase their solubility, stability and improve their pharmacokinetics as well as biodistribution [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of active principles can be solubilized within the PPO hydrophobic core [ 14 ] or can be conjugated to the PEO corona [ 15 ]. The loading of hydrophobic molecules in this type of PMs, with sizes usually smaller than 100 nm, can increase their solubility, stability and improve their pharmacokinetics as well as biodistribution [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) block copolymer (PEO-PPO-PEO) (commercially available as Pluronics and Poloxamers) is an amphiphilic block copolymer that can self-assembly into micelles in aqueous solution. Enormous study shown that the micellular structure is a practical approach for incorporating medicines, as it not only builds a drug delivery system but also applies to gene and cancer therapies [ 5 , 6 , 7 , 8 , 9 , 10 ]. The key attribute for the biological activity of Pluronic block copolymers is their ability to interact with multidrug-resistant cancer tumors with respect to various anticancer agents both in vitro and in vivo [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pluronic F-127, as categorized in a family containing more than 30 ABA-type triblock copolymers [ 28 , 29 ] with the components of 70% polyoxyethylene units and 30% polyoxypropylene blocks, is found to be the most commonly used polymer in pharmaceuticals due to its varied nature, one of the most important characteristics being the ability to form a thermoreversible gel at the temperature close to body temperature [ 29 , 30 , 31 ]. It has been suggested that the effect of thermogelation is due to the dehydration at the critical micelle temperature of polyoxypropylene (PPO) blocks.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in temperature would give a more significant result until the association of micelles occurs with each other at a specific temperature to form a gel. Moreover, another hypothesis has also been made suggesting that as the temperature increases, the modification of hydration spheres around the hydrophobic units could also induce the interactions along with the intramolecular hydrogen bonding effect [ 29 , 30 , 31 ]. From the results obtained, the average gelation temperature and gelation time decrease as the concentration of Pluronic F-127 increases, which leads to higher concentration of PPO responsible for the gelation effect.…”
Section: Discussionmentioning
confidence: 99%